2019
DOI: 10.1038/s41598-019-47322-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of psychological distress is stable in recent decades and follows an exponential pattern in the US population

Abstract: The prevalence of psychological distress is fairly stable in industrialised countries in recent decades, but the reasons for this stability remain unknown. To investigate the mechanisms underlying stability of psychological distress in the general population of the United States, we analysed the mathematical patterns of the distribution of psychological distress in recent decades. The present study utilised the Kessler psychological distress scale (K6) data from the 1997‒2017 United States National Health Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…In the face of threats, stress promotes environmental adaptation through an orchestrated neuro-hormonal and sympathetic response ( De Kloet et al., 2005 ; Ellis and Del Giudice, 2019 ). Psychological distress exists on a continuum in the population, from a transient and adaptive response to stressors, to those at the extreme end which may be at higher risk for mental disorders ( Kessler et al., 2010 ; Tomitaka et al., 2019 ). Intense psychological distress is a hallmark of mental disorders associated with poorer health outcomes and increased mortality risk ( Barry et al., 2020 ; Phillips, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of threats, stress promotes environmental adaptation through an orchestrated neuro-hormonal and sympathetic response ( De Kloet et al., 2005 ; Ellis and Del Giudice, 2019 ). Psychological distress exists on a continuum in the population, from a transient and adaptive response to stressors, to those at the extreme end which may be at higher risk for mental disorders ( Kessler et al., 2010 ; Tomitaka et al., 2019 ). Intense psychological distress is a hallmark of mental disorders associated with poorer health outcomes and increased mortality risk ( Barry et al., 2020 ; Phillips, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…and personal resources (i.e., personality, income, perceived control, etc.) modulate individuals´ level of psychological distress ( Byles et al., 2014 ; Drapeau et al., 2012 ; Tomitaka et al., 2019 ). Considering such factors from a diathesis-stress perspective, individuals’ response to stressors may be mediated by perceived threat intensity and the ability to cope with such external demands ( Beck and Dozois, 2011 ; Lazarus, 1966 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses of large-scale data have revealed that total scores in self-rated depression scales exhibit a common distribution in the general population. For example, as shown in Figures 1 A, 1B, and 1C, right-skewed distributions of total scores are similarly observed in the CES-D data from the Japanese Active Survey of Health and Welfare [ 12 ], the PHQ-9 data from the National Health and Nutrition Examination Survey [ 11 ], and the K6 data from the National Health Interview Survey in the United States (US) [ 14 ]. Generally, a score of ≧ 16 on the CES-D, a score of ≧ 10 on the PHQ-9, and a score of ≧ 13 on the K6 are defined as the cut-point for clinical depression.…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, responses to all depressive symptom items show a proportional relationship between response options, except for the lower end option [ 10 ]. These findings have been confirmed repeatedly by analyzing large-scale data collected from dozens of nationally representative surveys in the US, EU, and Japan [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation